Rotational Mechanism Model of the Bacterial V1 Motor Based on Structural and Computational Analyses - Singharoy, Abhishek; Chipot, Chris; Ekimoto, Toru; Suzuki, Kano; Ikeguchi, Mitsunori; Yamato, Ichiro; Murata, Takeshi (Frontiers in Physiology, 2019)
V1-ATPase exemplifies the ubiquitous rotary motor, in which a central shaft DF complex rotates inside a hexagonally arranged catalytic A3B3 complex, powered by the energy from ATP hydrolysis. We have recently reported a number of crystal structures of the Enterococcus hirae A3B3DF (V1) complex corresponding to its nucleotide-bound intermediate states, namely the forms waiting for ATP hydrolysis (denoted as catalytic dwell), ATP binding (ATP-binding dwell), and ADP release (ADP-release dwell) along the rotatory catalytic cycle of ATPase. Furthermore, we have performed microsecond-scale molecular dynamics simulations and free-energy calculations to investigate the conformational transitions between these intermediate states and to probe the long-time dynamics of the molecular motor. In this article, the molecular structure and dynamics of the V1-ATPase are reviewed to bring forth a unified model of the motor’s remarkable rotational mechanism.